A theory of distributed number - Dali, Myriam (Linguistik aktuell ;, 2021)
"The objective of this book is to develop a deeper understanding of the form and interpretation of number. Using insights from Generative syntax and Distributed Morphology, we develop a theory of distributed number, arguing that number can be associated with several functional heads and that these projections exist depending on the features they specify. In doing so, we make a strong claim for a close mapping between the syntactic structure and the semantics in the noun phrase, since each node corresponds to a different interpretation of number. Despite some technical implementations, the book is accessible to linguists working outside any particular syntax-semantic framework, since we propose generalizations that are applicable in many, if not all, models of grammar. The book focuses on Arabic, but also discusses a number of languages including English, French, Ojibwe, Blackfoot, Hebrew, Japanese, Korean, Chinese, Turkish, Persian, and Western Armenian"--